Centers for Disease Control and Prevention Public Health Response to Humanitarian Emergencies, 2007–2016 - Andrew T. Boyd; Susan T. Cookson; Mark Anderson; Oleg O. Bilukha; Muireann Brennan; Thomas Handzel; Colleen Hardy; Farah Husain; Barbara Lopes Cardozo; Carlos Navarro Colorado; Cyrus Shahpar; Leisel Talley; et al. (Emerging Infectious Diseases, 2017)
Humanitarian emergencies, including complex emergencies associated with fragile states or areas of conflict, affect millions of persons worldwide. Such emergencies threaten global health security and have complicated but predictable effects on public health. The Centers for Disease Control and Prevention (CDC) Emergency Response and Recovery Branch (ERRB) (Division of Global Health Protection, Center for Global Health) contributes to public health emergency responses by providing epidemiologic support for humanitarian health interventions. To capture the extent of this emergency response work for the past decade, we conducted a retrospective review of ERRB’s responses during 2007–2016. Responses were conducted across the world and in collaboration with national and international partners. Lessons from this work include the need to develop epidemiologic tools for use in resource-limited contexts, build local capacity for response and health systems recovery, and adapt responses to changing public health threats in fragile states. Through ERRB’s multisector expertise and ability to respond quickly, CDC guides humanitarian response to protect emergency-affected populations.